Transplante de células mononucleares da medula óssea modulam a expressão de fatores tróficos em modelo animal de epilepsia crônica induzida por pilocarpina - Zanirati, Gabriele Goulart (2013)
Epilepsy affects 1% of the world population and 30% of these patients are refractory to available medication. Stem cells host hope in the treatment of epilepsy. Given their ability to proliferate, differentiate and production of factors which may activate endogenous mechanisms to restore the injured brain. Knowing that the administration of bone marrow mononuclear cells (BMMC) in animals have therapeutic potential in an experimental model of epilepsy, the aim of this study is to investigate the mechanisms by which administered cells exert their beneficial. In order to better understand the mechanisms of action of transplanted cells, a comparative study was done to detect the expression of trophic factors as brain-derived neurotrophic factor (BDNF), glial cell-derived neurotrophic factor (GDNF), nerve growth factor (NGF), transforming growth factor beta (TGF-R) and vascular endothelial growth factor (VEGF) in hippocampi of each experimental groups by ELISA. Experimental model of epilepsy was induced by pilocarpine injection (320 mg/kg; ip). Seizures were scored by Racine s scale. The duration of SE was controlled with diazepan (10mg/kg; ip; 90 minutes after SE onset). Twenty-two days after SE, rats were randomly assigned into groups: Control, Pilo, Pilo+BMMC evaluated in periods 3, 7 and 14 days after transplant. BMMC groups received cell transplantation (obtained from EGFP C57BL/6 mice) via tail vein (1x107 cells, 100L). While control animals received saline instead of pilocarpine. Pilocarpine-treated animals were monitored for the presence of spontaneous seizures for 22 days (7 days prior to cell transplant). Our results showed that there was a change in the protein expression of BDNF, GDNF, NGF, TGF-R and VEGF in the hippocampus of epileptic animals treated with BMMC compared to untreated epileptic animals and control, with variations in the expression of each factor at different times after transplantation. The expression of BDNF, GDNF, NGF and VEGF was high and TGF-R1 reduced after transplantation of BMMC compared to untreated epileptic animals. However, there was no difference in the expression of these factors in untreated epileptic animals compared to control animals, except TGF-R1, which proved to be high in the group of untreated epileptic animals compared to control animals. The results of this study provide additional data on the potential benefit of BMMC as well as provide insight into the mechanism by which BMMC promote functional recovery in epileptic rats.